2016
DOI: 10.1007/s11356-016-7907-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the nitrogen dioxide concentrations in the boundary layer by using multi-axis spectroscopic measurements and comparison with satellite observations

Abstract: This study emphasizes on near surface observation of chemically active trace gases such as nitrogen dioxide (NO) over Islamabad on a regular basis. Absorption spectroscopy using backscattered extraterrestrial light source technique was used to retrieve NO differential slant column densities (dSCDs). Mini multi-axis-differential optical absorption spectroscopy (MAX-DOAS) instrument was used to perform ground-based measurements at Institute of Environmental Sciences and Engineering (IESE), National University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The results of the study showed that political stability has a significant positive impact on the stock market in both the short and long run. Our results are similar with the findings of [ 28 ] that investigated the impact of political instability on the stock market in Pakistan using monthly data from 2000 to 2016. The study used the ARDL approach to examine the long-run and short-run relationship between political instability and the stock market.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The results of the study showed that political stability has a significant positive impact on the stock market in both the short and long run. Our results are similar with the findings of [ 28 ] that investigated the impact of political instability on the stock market in Pakistan using monthly data from 2000 to 2016. The study used the ARDL approach to examine the long-run and short-run relationship between political instability and the stock market.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…AOD is a columnar amount and speaks to the termination of light because of the presence in the air of mist concentrates, permitting AOD to be taken as an intermediary for the particulate issue at surrounding levels. A few analyses have contemplated the relationship between PM 2.5 and AOD seen by satellite utilizing fine vaporized division and have indicated a solid association with both (e.g., Kumar et al 2007 ; Singh et al 2006 ; Khokhar 2006 , 2017 ). Figure 4 shows a guide of 28 days of MODIS determined AOD and arrived at the midpoint of throughout the long-term 2017–2020.…”
Section: Computation and Discussionmentioning
confidence: 99%
“…Exposure to high concentrations of nitrogen dioxide has been reported to cause damage to the respiratory system and aggravates bronchitis in some cases (Valavanidis et al, 2008;Ma et al, 2013;Khokhar et al, 2017). Furthermore, exposure to NO 2 has been considered the root cause of reduced lungs efficiency in infants (Trasande and Thurston, 2005) and exacerbating asthma among primary school children (Youssef Agha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%